The Body Image Concern Inventory: Validation in a multiethnic sample and initial development of a Spanish language version - Littleton, Heather (2008)
Dysmorphic appearance concern encompasses preoccupation with a perceived appearance defect, defect checking and camouflaging, and social avoidance. The current study sought to evaluate the internal consistency, factor structure, and convergent validity of a measure of dysmorphic appearance concern, the Body Image Concern Inventory, as well as evaluate the psychometric properties of a Spanish version of the instrument. Women recruited as part of a reproductive clinic based clinical trial completed the BICI and other self-report measures of distress. A total of 1,043 women completed the measures in English (M = 29 years, range = 18–55 years) and 573 women completed the measures in Spanish (M = 32 years, range = 18–55 years). Both the English and Spanish BICI were internally consistent and correlated moderately with measures of current psychological distress (STAI-S, CES-D). Confirmatory factor analyses replicated the measure’s proposed factor structure. Applications of the BICI for future research are discussed.